The relationship between subjective well-being levels and physical self-perception and eating attitudes of students receiving sports education: The relationship between subjective well-being, physical self-perception and eating attitudes - Çakmak Yıldızhan, Yasemin; Yazıcı, Mehmet (Progress in Nutrition, 2020)
The study aims to investigate students’ physical selves, eating attitudes and subjective well-beings besidesthe predictive status of their physical self and eating attitude in subjective well-being. Method: The researchwhich has been designed on the basis of relational research method was conducted with 267 participants fromphysical education and sports schools. The data of the research consist of participants’ demographic information (the department that they study, grade level, gender), Physical Self Inventory scores, Eating Attitude Test scores, and Subjective Well-Being Scale scores. Descriptive analysis, Pearson Correlation and regression tests have been used for data analysis. Results: As a result of the analyzes, it is found that subjective well-being levels of the participants are moderate, 26.6% are at risk of eating attitude disorder, that the physical self, general self, physical condition and sport competence perceptions of physical self-perception sub-dimensions are moderate, and that physical fitness and physical strength perceptions were low. In addition, it is observed that there is a weak negative correlation between subjective well-being and eating attitude behavior, a weak positive correlation between subjective well-being and general self, physical self, physical condition and physical attraction perceptions, a moderate negative correlation between subjective well-being and physical strength perception, no significant relationship between subjective well-being and sport competence perception, and that eating attitude and physical self-perception are significant predictors of subjective well-being and explain 42% of the total variance.